Australian Nitidulinae: general review with descriptions of new genera and species (Coleoptera: Nitidulidae) - Lawrence, John F. (Zootaxa, 2019)
The classification of the subfamily Nitidulinae is reviewed, as it applies to those species occurring within Australia and its territories. Comments are made concerning the currently recognised tribes and generic “complexes” within this subfamily, Australian genera are briefly discussed, with reference to recent and proposed changes in their classification, and several new genera and species are described. The following new taxa are described: Aenigmoronia echinodes, gen. & sp. nov., Australycra similis, sp. nov., Austronitidula multimaculata, gen. & sp. nov., Cychramus splendidus, sp. nov., Lasiodites howensis, sp. nov. and Temnelytron nigrum, gen. & sp. nov. The following synonymy is proposed: Stelidota nigrovaria (Fairmaire, 1849) (= Aethinodes variabile Lea, 1921), syn. nov. The genus Testudoraea Kirejtshuk, 1986, stat. nov., is recognised as a distinct genus, and Perilopsis australis Kirejtshuk, 1990 is considered to be an unnecessary replacement name for Testudoraea flava Kirejtshuk, 1986.